Meniscal repair in the elite athlete: Results of 45 repairs with a minimum 5-year follow-up - Logan, M.; Watts, M.; Owen, J.; Myers, P. (The American Journal of Sports Medicine, 2009)
Background The preservation of meniscal tissue is important to protect joint surfaces.